2022
DOI: 10.3390/md20030174
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Impact of Brown Seaweed Ascophyllum nodosum and Fucus vesiculosus Extract on Metabolic and Inflammatory Response in Overweight and Obese Prediabetic Subjects

Abstract: The objective of the present study was to test whether a brown seaweed extract rich in polyphenols combined with a low-calorie diet would induce additional weight loss and improve blood glucose homeostasis in association with a metabolic and inflammatory response in overweight/obese prediabetic subjects. Fifty-six overweight/obese, dysglycemic, and insulin-resistant men and women completed a randomized, placebo-controlled, double-blind, and parallel clinical trial. Subjects were administrated 500 mg/d of eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…Once more, the test product contained a mixture of compounds making the attribution of the observed properties to the (poly)phenols impossible. One additional study evaluated the potential of a brown (poly)phenol-rich seaweed extract (Ascophyllum nodosum and Fucus vesiculosus; 0.5 g/day for 12 weeks) in combination with a low-calorie diet in overweight/obese individuals with prediabetes [30]. Although some inflammatory markers were attenuated, the authors did not detect significant changes in blood glucose, insulin levels or glycated hemoglobin in the brown seaweed intervention group (N = 27) when compared with the placebo group (N = 29).…”
Section: Results From Verymentioning
confidence: 99%
“…Once more, the test product contained a mixture of compounds making the attribution of the observed properties to the (poly)phenols impossible. One additional study evaluated the potential of a brown (poly)phenol-rich seaweed extract (Ascophyllum nodosum and Fucus vesiculosus; 0.5 g/day for 12 weeks) in combination with a low-calorie diet in overweight/obese individuals with prediabetes [30]. Although some inflammatory markers were attenuated, the authors did not detect significant changes in blood glucose, insulin levels or glycated hemoglobin in the brown seaweed intervention group (N = 27) when compared with the placebo group (N = 29).…”
Section: Results From Verymentioning
confidence: 99%
“…Both in vitro [ 38 ] and in vivo [ 39 ] experiments have indicated that A. nodosum extract has antioxidant and anti-inflammatory properties; therefore, long-term consumption of A. nodosum extract polyphenols may have health benefits. Vodouhè et al [ 44 ] reported that consumption of brown algae crude extract of A. nodosum and F. vesiculosus at a dosage of 500 mg/day for 12 weeks had no effect on body weight or blood glucose; however, early attenuation of the inflammatory response was observed in individuals with overweight/obesity, dysglycemia, and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, regular consumption of fruits and vegetables as rich sources of natural antioxidants were reported to decline the risk of DM. In addition, antioxidant compounds like polyphenols have hypoglycaemic effects through the inhibition of carbohydrate digestive enzymes and improving the sensitivity of tissues to insulin hormone 8–10 . Finding alternative functional supplements such as antioxidant compounds to improve the quality of clinical therapies may have beneficial effects against the side effects of chemical drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicated that seaweed polyphenols may have higher biological and pharmacological properties in comparison with other plant‐derived phenolic compounds 10–13 . Algae polyphenol‐rich extracts (APREs) were reported to improve the blood glucose and serum lipids levels in a concentration‐dependent manner 14–16 .…”
Section: Introductionmentioning
confidence: 99%